Using dwell time as an implicit measure of usefulness in different task types - Liu, Chang; Liu, Jingjing; Belkin, Nicholas J; Cole, Michael J; Gwizdka, Jacek (Proceedings of the American Society for Information Science and Technology, 2011)
In this study, we attempted to use dwell time on content pages as a predictor of document usefulness, and evaluated the prediction performance in different types of tasks. A user study was conducted to address this research problem. A total of 32 participants conducted searches associated with 4 different tasks, varying along several task type dimensions. In the study, participants were asked to save documents that were useful for the tasks during the searches. Participants' information-seeking activities were recorded. Using the logged dataset, we used the recursive partitioning method to identify the best threshold (cutoff point) of dwell time to predict which pages would be useful, i.e., be saved by the users. We examined the differences in the threshold and compared the prediction performance for each type of task. Our results indicate that the threshold should be developed according to the type of task users are working on. While the prediction performance using dwell time as the only indicator of document usefulness is acceptable for Factual tasks, it is not good for Intellectual tasks. Our results have implications on IR system design.
5 citations (Crossref) [2023-10-31]
Keywords: Dwell time; Personalization; Task type; Usefulness prediction; dept.ils

Search task difficulty: the expected vs. the reflected - Liu, Jingjing; Belkin, Nicholas J (International ACM SIGIR Conference on Research and Development in Information Retrieval, 2011)
We report findings on how the user's perception of task difficulty changes before and after searching for information to solve tasks. We found that while in one type of task, the dependent task, this did not change, in another, the parallel task, it did. The findings have implications on designing systems that can provide assistance to users with their search and task solving strategies.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Dependent tasks; Designing systems; Predicted difficulty; Reflected difficulty; Searching for informations; Task difficulty; Task type; User's perceptions; dept.ils

Understanding searchers' perception of task difficulty: Relationships with task type - Liu, Jingjing; Liu, Chang; Yuan, Xiaojun; Belkin, Nicholas J (Proceedings of the American Society for Information Science and Technology, 2011)
We report findings that help us better understand the difficulty of tasks which involve information seeking, retrieving, gathering, and use. We examined the data gathered from two interactive information retrieval user studies on how users' perception of task difficulty changes before and after searching for information to solve tasks, and how the difficulty of tasks relates with users' background, previous experience with the tasks, and knowledge of the task topics, etc. The two studies employed carefully designed tasks with different types along several dimensions: task structure (subtasks being dependent upon or parallel with each other), task goal in quality (being specific or amorphous), and naming (being named or unnamed). It was found that while in some types of tasks, users' perceptions of task difficulty did not change before and after working on the tasks, in others, this did, either increasing or decreasing. Specifically, in the dependent-structured task, this did not change. In the parallel-structured or specific/named task, it decreased. In the amorphous/unnamed task, it increased. We also found that users' background factors do not normally correlate with their perceived task difficulty, or perceived difficulty change. In addition to helping understand the dynamic and complex nature of task difficulty, our findings have implications for system design that can provide assistance to users with their search and task solving strategies.
6 citations (Crossref) [2023-10-31]
Keywords: Expected difficulty; Reflected difficulty; Task difficulty; Task type; dept.ils

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-473-790-983-166 tex.type: [object Object]
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib